EP1029 A preliminary study of genetic susceptibility and treatment related gene profiling in chinese ovarian cancer patients. (1st November 2019) - Feng, Z; Wen, H; Ju, X; Chen, X; Wu, X
Abstract : Introduction/Background: The purpose of our study was to presentgenetic susceptibility and treatment related gene profiling in Chinese ovarian cancer patients. Methodology: We have applied next-generation sequencing in consecutive patients who underwent primary surgery for ovarian cancer since 2016 at our institution. 241 patients have been enrolled for blood tests so far. Paired tumor samples from 62 patients have been tested for somatic deleterious mutations. Results: The median (range) age of patients was 54 (35–83) years old. 27.4% (66/241) patients had germline deleterious mutations. The most frequently reported genes were as follows: 29 (12.8%) BRCA1 mutations, 19 (7.9%) BRCA2 mutations, 6 (2.5%) RAD51C mutations, and 6 (2.5%) RAD51D mutations. Other mutated genes investigated included BRIP1 (2), CHEK2 (2), RAD50 (2), MRE11A (2), PMS1 (1) and MLH1 (1). 4 patients had dual gene mutation, that is BRCA1/PMS1, BRCA1/RAD50, BRCA2/BRIP1, and BRCA2/RAD51D. For the paired tumor samples, 19 (30.6%) deleterious TP53 mutations were identified, 4 patients had somatic BRCA1 mutations and 1 patient had somatic BRCA2 mutation. Conclusion: Our results suggest a comprehensive profiling for Chinese ovarian cancer patients. Somatic genetic test could help better stratify patients for individualized treatment. Disclosure: Nothing to disclose.